Study on Flow Behavior in Terminal Bronchus of Human Lung for Porous Medium - Akhtera, Sadiya; Ahmmed, MU (GANIT: Journal of Bangladesh Mathematical Society, 2022)
Flow simulation along human lung channel is one of the interests of investigation in fluid dynamics. We have studied flow phenomena of 11th generation of human lung as porous medium. The governing equations of porous medium have been solved numerically using finite difference scheme. The effect of different flow parameters are illustrated graphically. It is observed that the flow rate increases for increasing the value of pressure gradient, the porosity effect, effective viscosity and the dimensionless parameter . The numerical experiment for non-porous medium is also studied. It is found that the flow rate increases in porous medium compared with non-porous medium. GANIT J. Bangladesh Math. Soc. 42.1 (2022) 069- 080